Analysis of the Determinants of Poverty in the Province of Papua - Aditya Romadhon, M. (Lafadz Jaya Publisher, 2024)
Poverty is still an interesting issue to discuss, because it is still a major problem faced by all countries, both developed and developing countries. This study aims to analyze the determinants of the poverty rate in Papua Province. The data used in this study are secondary data, while the analysis method used is the panel data regression method from 2017-2021 in Papua Province. This study uses dependent variables and independent variables, the dependent variable used is poverty and the independent variables include the Gini index, average years of schooling, construction cost index, and open unemployment rate. The results showed that the Gini index, construction cost index, and open unemployment rate had a positive and significant effect on the poverty rate in Papua Province, while the average years of schooling had a negative and significant effect on the poverty rate in Papua Province.